The Process of Musical Interpretation and the Play-Element in Music (International Journal of Scientific Research and Management (IJSRM), 2021)
The article is devoted to examination of such phenomenon as musical interpretation, which incorporates various aspects of composer’s and performer’s creativity, listener’s perception, different styles of musical art, creative communication in music. The attempt to find the traits of the play-element in the process of musical interpretation may help to define the mechanisms, through which “play” activity in music in general is realized. Systematic approaches of scholars of the play-element and theorists of artistic interpretation present great possibilities to conduct such a research. Examination of theoretical points of view on beforementioned problems allowed to reach a conclusion that the play-element is inherent to the music and is expressed in the process of interpretation. This happens in the framework of the system “composer – performer – sound director – listener”, in which artistic interpretation plays a significant role.